GmABR1 encoding an ERF transcription factor enhances the tolerance to aluminum stress in Arabidopsis thaliana - Wang, Hongjie; Li, Cheng; Wang, Lidan; Zhong, Hongying; Xu, Xin; Cheng, Yanbo; Nian, Hai; Liu, Wenhua; Chen, Pei; Zhang, Aixia; Ma, Qibin (Frontiers in Plant Science, 2023)
The ethylene response factor (ERF) transcription factors, which is one of the largest transcription factor families in plants, are involved in biological and abiotic stress response and play an important role in plant growth and development. In this study, the GmABR1 gene from the soybean inbred line Zhonghuang24 (ZH24)×Huaxia 3 (HX3) was investigated its aluminum (Al) tolerance. GmABR1 protein has a conserved domain AP2, which is located in the nucleus and has transcriptional activation ability. The results of real-time quantitative PCR (qRT-PCR) showed that the GmABR1 gene presented a constitutive expression pattern rich in the root tip, stem and leaf tissues of HX3. After Al stress, the GmABR1 transcript was significantly increased in the roots. The transcripts of GmABR1 in the roots of HX3 treated with 50 µM AlCl3 was 51 times than that of the control. The GmABR1 was spatiotemporally specific with the highest expression levels when Al concentration was 50 µM, which was about 36 times than that of the control. The results of hematoxylin staining showed that the root tips of GmABR1-overexpression lines were stained the lightest, followed by the control, and the root tips of GmABR1 RNAi lines were stained the darkest. The concentrations of Al3+ in root tips were 207.40 µg/g, 147.74 µg/g and 330.65 µg/g in wild type (WT), overexpressed lines and RNAi lines, respectively. When AlCl3 (pH4.5) concentration was 100 µM, all the roots of Arabidopsis were significantly inhibited. The taproot elongation of WT, GmABR1 transgenic lines was 69.6%, 85.6%, respectively. When treated with Al, the content of malondialdehyde (MDA) in leaves of WT increased to 3.03 µg/g, while that of transgenic Arabidopsis increased from 1.66-2.21 µg/g, which was lower than that of WT. Under the Al stress, the Al stress responsive genes such as AtALMT1 and AtMATE, and the genes related to ABA pathway such as AtABI1, AtRD22 and AtRD29A were up-regulated. The results indicated that GmABR1 may jointly regulate plant resistance to Al stress through genes related to Al stress response and ABA response pathways.